Pemahaman Remaja Desa Batang Gunung terhadap Moderasi Beragama dalam Studi Kasus di Desa Batang Gunung, Kecamatan Lembah Melintang Kabupaten Pesaman Barat - Dana, Rinta Sari; Harahap, Indra; Nasution, M. Ali Azmi (Lembaga Yasin AlSys, 2023)
This thesis is entitled Knowledge of Youth About Religious Moderation in Batang Gunung Village, Lembah Melintang District, Pasaman Barata Regency. The formulation of the problem is how is the concept of religious moderation and how is the knowledge of adolescents in the Batang Gunung village, sub-district across West Pasaman district about religious moderation. There are also findings from the results of this study indicating that Adolescent Knowledge About Religious Moderation in Batang Gunung Village, Lembah Melintang District, Pasaman Barata Regency is a process of explaining the purpose and importance of having knowledge of religious moderation, so that it is easy to know a difference, and to create love in society religion, protecting the rights of shared beliefs, giving freedom to believe in beliefs according to one's conscience, and realizing peace in social life. The results of this study indicate that the majority of respondents have an